Managing Tibia Metaphyseal Bone Defect in Total Knee Arthroplasty - Ong, Lik Han; Rutel, Ankimtay; Jaffar, Mohd Shahrul Azuan; Sabaruddin, Abdullah; Bong, Chun Haw; Tan, Kean Tee; Prashant Rao, Reuben; Kamaruddin, Faris (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2023)
INTRODUCTION: Bone defect in the tibia metaphyseal region can present a challenge in both primary total knee arthroplasty (TKA) and revision total knee arthroplasty. In our experience of managing tibia metaphyseal bone defect in total knee arthroplasty (TKA), we use bone cement alone if defect was ≤30% width and ≤5mm deep, cement and screw if depth was 5-10mm, and metal augment if depth was >10mm or width ˃30%. We would like to report the results of simple algorithm which can provide good or comparative outcome for tibia component in both primary and revision TKAs.